PERANCANGAN TEKSTIL MARBLING PADA MATERIAL DENIM UNTUK PRODUK SEPATU BOOTS WANITA - Vincentia Natasha Evania (Texture:Art and Culture Journal, 2022)
ABSTRACTThe project background of this design final project is that the marbling technique has been widely known in the 15th century. This technique was initially applied to paper and now began to be applied to textile media. The marbling technique which has quite good potential in providing a variety of decorations to textiles has attracted the attention of the author to make technical innovations in exploring and innovating marbling techniques on denim material for women's boots.The purpose of designing this project is to produce marbling products on textile media with tapak dara flower visuals that can add variety to clothing complementary products that have distinctive and different characters with consideration of the function for textile motifs on women's boots.The method used in this design project is the design method. This method consists of 3 stages, namely the design method, design concept and visualization. The results of this design resulted in 8 motif designs, all of the motif designs processed the visual of the tapak dara flower as the main motif with the concept of coloring the forecasting trend 2019-2020: Cortex which produces bright colors.